In vitro clonal micropropagation of selected Malus niedzwetzkyana Dieck forms demonstrating high resilience when introduced into urban environments - A. P. Belanova; Yu. G. Zaytseva; E. M. Lyakh (Труды по прикладной ботанике, генетике и селекции)
Background. Currently, the use of an interdisciplinary approach based on a combination of traditional introduction methods and clonal micropropagation techniques makes it possible to solve one of the key problems of introduction – the establishment of bioresource collections consisting of selected plant accessions with valuable agronomic traits and resistance to unfavorable urban environments. Materials and methods. A plant introduction study resulted in identifying seven specimens of Malus niedzwetzkyana Dieck with resilience to urban environments, high rate of crown development, and longevity. They served as source material for the development of a clonal propagation protocol and in vitro preservation of selected genotypes of this species. Results. It was shown for M. niedzwetzkyana that the most favorable time for taking its plant material for introduction into in vitro culture is the beginning of the active growth of vegetative shoots after flowering. The most optimal sterilization technique for such plant material was a stepwise regime using alcohol, sodium hypochlorite, and silver nitrate: it provided from 50 to 70% of sterile explants and the maximum percentage of meristem proliferation. Combining 0.8 mg/L of benzylaminopurine (BAP) with 0.14 mg/L of indole-3-butyric acid (IBA) at the stage of microclonal propagation ensured a significant increase of the reproduction coefficient (on average up to 5.3 ± 0.7) and an improvement in morphometric parameters of microshoots; the maximum frequency of shoot proliferation was 100%. The yield of shoots adapted to ex vitro conditions was 90%. Conclusion. The developed clonal micropropagation protocol made it possible to introduce selected M. niedzwetzkyana forms into in vitro culture and reproduce them in order to set up a resource base for further fundamental and applied research into the system of the genus Malus Mill.